Contribution of exosite occupancy by heparin to the regulation of coagulation proteases by antithrombin - Yang, Likui; Manithody, Chandrashekhara; Qureshi, Shabir H.; Rezaie, Alireza R. (Thrombosis and Haemostasis, 2010)
Heparin promotes the antithrombin (AT) inactivation of factors IXa (fIXa) and Xa (fXa) through a conformational activation of the serpin and also by a template mechanism in the presence of physiological levels of Ca2+. Recently, it was reported that heparin induces conformational changes in the active-sites of fIXa and fXa, raising the possibility that heparin also modulates the reactivity of these proteases with AT by this mechanism. To test this possibility, we prepared an AT mutant in which four critical heparin-binding residues of the serpin (Arg-45, Arg-46, Lys-114, and Arg-129) were replaced with non-basic residues. This mutant lost its affinity for heparin, but retained its normal reactivity with coagulation proteases. Thus, the high-affinity AT-binding pentasaccharide fragment of heparin had no cofactor effect on the reactivity of the AT mutant with coagulation proteases. Full-length heparinconcentration dependence of the AT inhibition of fIXa and fXa revealed that in contrast to a greater than 4–5 orders of magnitude accelerating effect for heparin on the AT inhibition of fIXa and fXa, heparin exhibits a negligible cofactor effect (<2-fold) on the mutant AT inhibition of these proteases. The same results were obtained for the mutant AT inhibition of thrombin and factor VIIa, however, heparin accelerated the mutant AT inhibition of factor XIa ~10-fold. We conclude that, with the exception of factor XIa, heparin-mediated conformational modulation of the active-sites of coagulation proteases makes a minor contribution to the regulation of these proteases by AT.
Keywords: Antithrombin; heparin; coagulation; factor Xa; factor IXa; thrombin